Assessment of Compliance by Mental Health Professionals on the General Adult Inpatient Wards in Mersey Care NHS Foundation Trust With DVLA Guidelines on Driving Restrictions for Individuals With a Mental Health Condition - Kareem Salem; Declan Hyland (BJPsych Open, 2025)
Aims: Individuals with a severe and enduring mental illness may pose a significant risk to themselves and others when they drive, particularly if in a state of relapse. The DVLA provides guidance for driving for individuals with mental disorders. It provides guidance for medical professionals caring for such patients to determine during their assessments the potential for safe driving and restrictions, if any. Patients admitted to a psychiatric ward who drive should be informed of the DVLA guidance and any restrictions on driving prior to discharge and such discussions should be documented in the inpatient’s medical record. This audit aimed to assess compliance of mental health professionals on the general adult inpatient wards with DVLA guidelines regarding patients about driving restrictions and whether such discussions are documented in the inpatient’s medical record.